The moderating effects of group culture on the relationship between personality traits and customer oriented-behavior in the health tourism hospitals in Malaysia - Ong, Choon Hee; Johari, Husna (Elite Hall Publishing House, 2014)
The purpose of this paper is toexamine the moderating effect of group culture on the relationship between personality traits and customer-oriented behavior in the health tourism hospitals.This study involved 343 nurses in the 13 health tourism hospitals in Malaysia.Administered on-site questionnaire survey was used as the main method of data collection.Hierarchical regression analy sis wasperformed and found statistical significant relationship between personality traits and customer-oriented behavior as well as positive moderating effects of group culture.